Coleus Amboinicus (Bangun-Bangun Leaves) and Stolephorus Commersonii (Anchovies) Biscuit in Increasing Iron Intake in Adolescent Girls - Bernardin Dwi Fontani; Fatmalina Febry; Rostika Flora; Windi Indah Fajar Ningsih (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Adolescent girls are more susceptible to anemia so good nutritional intake is needed to meet these iron needs. to meet iron needs in adolescents. Bangun-bangun leaves biscuits and anchovies that are rich in iron can be a solution to meet the iron needs of adolescent girls. This study aimed to determine the selected formulation, the effect of adding bangun-bangun leaves and anchovies to biscuits and the iron content of biscuits. This research was an experimental research, with the RAL (Complete Randomized Design) research method. Laboratory tests on the products of bangun-bangun leaves and anchovies were conducted to determine the iron content contained in the products. Data collection was conducted on 22 fairly trained panelists, to test the organoleptic of the products of bangun-bangun leaves and anchovies. Based on the results of the hedonic test, F3 biscuits were the most preferred formula compared to other formulations. Based on statistical tests, data was obtained that there was a significant difference (p <0.05) between the color, aroma, taste and texture of all formulas. The results of laboratory tests showed that the more bangun-bangun leaves and anchovies were added, the higher the iron content in the biscuits. By consuming F3 biscuits as additional food, it could meet the iron needs of adolescent girls, which was 15% of the total daily requirement. F3 biscuits can be an alternative substitute for snacks or supplementary food for adolescent girls to meet their iron intake needs so that they can prevent anemia.